Educação permanente em saúde: Estratégia para implantar protocolos de segurança do paciente em um hospital público - Dal Pozzo, Monique Junges (Universidade do Vale do Rio dos Sinos, 2014)
The Application of Nursing Care Protocols (NCP) seeks to qualify the care practices, and for this, the Permanent Health Education (PHE) is used as a working tool, to promote knowledge about patient safety. Objectives: Implement in Hospital Universitário de Canoas - RS (HU), NCPs adopted in Network Mãe de Deus, with view to certification process; verify how technical team identifies the application od NCPs; identify contributions that NCPs may bring to HU; propose a PHE plan towards the implementation of NCP. Method: Study conducted with ten practical nurses, exploratory-descriptive, qualitative approach. Results: From the focus groups, categories were emerged: interference of the hospital infrastructure in nursing care; interference of nursing staff work in patient care; PHE as a modifier in the daily work of the nursing staff; development of a tool that promotes the implementation of the International Safety Goals and a PHE cue plan towards the implementation of NCPs. Conclusion: This study will serve as a guide to implement improvements in care practice. There are difficulties, but the work processes that depend on people are happening.
Keywords: Protocolos assistenciais; Segurança; Qualidade no cuidado; Enfermagem; Cuidado em enfermagem; Educação permanente em saúde; Care protocols; Safety; Quality care; Nursing; Nursing care; Permanent health education; ACCNPQ::Ciências da Saúde::Enfermagem